PENGARUH BULAN RAMADHAN TERHADAP RETURN PASAR SAHAM DI BURSA EFEK INDONESIA (1425H-1434H) - Aprida Rusmayanti; Meina Wulansari Yusniar; Asrid Juniar (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
The phenomenon of monthly effect is when the desire of financiers on the liquidity of stock changes from month to month in a year. This monthly effect of course is contrary to the concept of efficient markets, but it gives confidence to investors that there is still a gap to benefit by using information of price and sales volume in past. Ramadhan effect is monthly effect, it has been investigated several time in Islamic countries and it was found that there was a difference in market return during Ramadhan month rather than during any other months. The purpose of this study was to describe the effect of Ramadhan on the stock market return in the Indonesia Stock Exchange (IDX). Ramadhan effect, is a seasonal anomaly in the financial markets, when stock returns during Ramadhan is different from the other. The unit of analysis used in this study is a JSX composite of 1425H-1434H (February 21, 2004 -3 November 2013). The statistical method used to test the hypothesis is nonparametric test (sign test), because the data are not normally distributed. The results showed that there was no influence of Ramadhan on the stock market return in the Indonesia Stock Exchange. The cause of the lack of differences in returns among others due to the stability of the value of JSX Composite which is basic calculation of returns, but it also may be due to cultural differences and different conditions during the month of Ramadhan between Indonesia and other countries. Investor behavior changes that occur in other countries during Ramadhan does not occur in Indonesia due to the investors’s composition in Indonesia is still dominated by foreign and institutional investors. The results of this study indicate that the capital market in Indonesia efficient in weak form, because the pattern of stock price movement is random or unpredictable